Prevention of Bullying Behavior Tendencies Among Adolescents in Surakarta City - Rejekiningsih, Triana; Sumaryati, Sri; Sari, Dewi Ika; Ariana, Yudi (Universitas Negeri Malang, 2025)
The purpose of this study is to analyze the forms of bullying, influencing factors, and efforts to address bullying among students. This study used a mixed methods approach, combining qualitative and quantitative approaches. The results indicate that the most common forms of bullying among students are verbal bullying, cyberbullying, and physical bullying. Verbal bullying has a relatively high prevalence rate of 22.1 percent to 59.4 percent, cyberbullying has a moderate prevalence rate of 23.2 percent to 37.4 percent, and physical bullying has a low prevalence rate of 10 percent to 16.1 percent. Bullying among students is influenced by two factors: psychosocial factors, including emotional regulation and empathy, and social environmental factors, including peer pressure, interaction culture, and digital ethics. Prevention and handling of bullying at the school level can be achieved through several strategies: internalizing anti-bullying attitudes through character education, strengthening reporting and monitoring systems, and cross-sector collaboration to address bullying.